Simplified woven fabric geometry for tensile and bending analysis / Ungku Nur Ainaa Ungku Mohd Aziz, Suzaini Abdul Ghani and Mohamad Faizul Yahya - Ungku Mohd Aziz, Ungku Nur Ainaa; Abdul Ghani, Suzaini; Yahya, Mohamad Faizul (Universiti Teknologi MARA (UiTM), 2022)
This paper introduced a simplified finite element analysis (FEA) tensile model to replace the actual prototype with the FEA software. FEA was performed using commercially available ABAQUS software. FEA is a computerized method of predicting how a product reacts to real-world forces, vibrations, heat, fluid flow, and other physical effects. Furthermore, fabric performance can expect by using FEA in textile testing. This project aims to determine the tensile and bending analysis of the plain-woven fabric using ABAQUS software. The fibre modulus was configured 10 % and 20 % lower than the initially configured modulus. The mesh size is reduced to 20 % and 40 % to determine the stress and strain curve and analyze the bending model. The results showed that the stress-strain curve would be affected as the modulus and mesh size decreases.